FEATURES OF THE RELATIONSHIP BETWEEN THE GENERAL AND DEONTOLOGICAL CULTURE OF A PERSON (Universal International Scientific Journal, 2026)
The characteristics of the connections between the general and deontological culture of a person, as well as duty, responsibility, moral rules and standards of professional etiquette, are described.
Keywords: deontology, deontological preparation, spiritual satisfaction, personality, duty, responsibility, ethical rules and professional etiquette, highly spiritual.